Birds repurpose the role of drag and lift to take off and land - Diana D. Chin (Nature Portfolio, 2019)
Recent work has suggested that lift and drag may be employed differently in slow, flapping flight compared to classic flight aerodynamics. Here the authors develop a method to measure vertical and horizontal aerodynamic forces simultaneously and use it to quantify lift and drag during slow flight.